Islamic Religious Education at Pre-Baligh Age According to Ibn Qayyim Al Jauziy - Euis Sufi Jatiningsih; Imas Kania Rahman; Hendri Tanjung (al-Afkar, Journal For Islamic Studies, 2023)
This article discusses the subject matter of curriculum for pre-baligh children's education in terms of the thoughts of Ibn Qayyim Al Jauzi and is enriched with other thoughts that refer to Al- Qur'an and hadith. This study uses the library research method, especially in the book Tuhfah Al-Maudud bil Ahkamil Maulud, written by Ibn Qayyim Al-Jauzy. The results of the study show that Imam Ibn Qayyim Al-Jauzi is very detailed in detailing what material or curriculum should be given to children, even from 0 to 2 years old. It was also found that the choice of the word "ghulam" in various hadiths describes the interactions of the Prophet Sallallaahu 'Alaihi Wasallam with young children, describing what educational materials should be delivered to them. In addition, the authors can formulate that the educational material for children at pre-battle age includes education on aqeedah, morals, or adab, character, faith, self-confidence, amar ma'ruf nahyi munkar, and awareness to defend religion.